Candidate genes for polycystic ovary syndrome are regulated by TGFβ in the bovine foetal ovary. Issue 6 (12th April 2022) - Azumah, Rafiatu; Liu, Menghe; Hummitzsch, Katja; Bastian, Nicole A; Hartanti, Monica D; Irving-Rodgers, Helen F; Anderson, Richard A; Rodgers, Raymond J
Abstract: STUDY QUESTION: Could changes in transforming growth factor β (TGFβ) signalling during foetal ovary development alter the expression of polycystic ovary syndrome (PCOS) candidate genes leading to a predisposition to PCOS? SUMMARY ANSWER: TGFβ signalling molecules are dynamically expressed during foetal ovary development and TGFβ1 inhibits expression of the androgen receptor ( AR ) and 7 ( INSR, C8H9orf3, RAD50, ERBB3, NEIL2, IRF1 and ZBTB16 ) of the 25 PCOS candidate genes in foetal ovarian fibroblasts in vitro, whilst increasing expression of the AR cofactor TGFβ-induced transcript 1 ( TGFB1I1 or Hic5). WHAT IS KNOWN ALREADY: The ovarian stroma arises from the mesonephros during foetal ovary development. Changes in the morphology of the ovarian stroma are cardinal features of PCOS. The ovary is more fibrous and has more tunica and cortical and subcortical stroma. It is not known why this is and when this arises. PCOS has a foetal origin and perhaps ovarian stroma development is altered during foetal life to determine the formation of a polycystic ovary later in life. PCOS also has a genetic origin with 19 loci containing 25 PCOS candidate genes. In many adult tissues, TGFβ is known to stimulate fibroblast replication and collagen deposition in stroma, though it has the opposite effect in the non-scaring foetal tissues. Our previous studies showed that TGFβ signalling molecules [TGFβs and their receptors, latent TGFβ binding proteins (LTBPs) and fibrillins, which are extracellular matrix proteins that bind LTBPs] are expressed in foetal ovaries. Also, we previously showed that TGFβ1 inhibited expression of AR and 3 PCOS candidate genes ( INSR, C8H9orf3 and RAD50 ) and stimulated expression of TGFB1I1 in cultured foetal ovarian fibroblasts. STUDY DESIGN, SIZE, DURATION: We used Bos taurus for this study as we can ethically collect foetal ovaries from across the full 9-month gestational period. Foetal ovaries (62–276 days, n = 19) from across gestation were collected from pregnant B. taurus cows for RNA-sequencing (RNA-seq) analyses. Foetal ovaries from B. taurus cows were collected (160–198 days, n = 6) for culture of ovarian fibroblasts. PARTICIPANTS/MATERIALS, SETTING, METHODS: RNA-seq transcriptome profiling was performed on foetal ovaries and the data on genes involved in TGFβ signalling were extracted. Cells were dispersed from foetal ovaries and fibroblasts cultured and treated with TGFβ1. The effects of TGFβ regulation on the remaining eight PCOS candidate genes not previously studied ( ERBB3, MAPRE1, FDFT1, NEIL2, ARL14EP, PLGRKT, IRF1 and ZBTB16 ) were examined. MAIN RESULTS AND THE ROLE OF CHANCE: Many TGFβ signalling molecules are expressed in the foetal ovary, and for most, their expression levels increased accross gestation ( LTBP1/2/3/4, FBN1, TGFB2/3, TGFBR2/3 and TGFB1I1 ), while a few decreased ( FBN3, TGFBR3L, TGFBI and TGFB1 ) and others remained relatively constant ( TGFBRAP1, TGFBR1 and FBN2 ). TGFβ1 significantly decreased expression of PCOS candidate genes ERBB3, NEIL2, IRF1 and ZBTB16 in cultured foetal ovarian fibroblasts. LARGE SCALE DATA: The FASTQ files, normalized data and experimental information have been deposited in the Gene Expression Omnibus (GEO) accessible by accession number GSE178450 . LIMITATIONS, REASONS FOR CAUTION: Regulation of PCOS candidate genes by TGFβ was carried out in vitro and further studies in vivo are required. This study was carried out in bovine where foetal ovaries from across all of the 9-month gestational period were available, unlike in the human where it is not ethically possible to obtain ovaries from the second half of gestation. WIDER IMPLICATIONS OF THE FINDINGS: From our current and previous results we speculate that inhibition of TGFβ signalling in the foetal ovary is likely to (i) increase androgen sensitivity by enhancing expression of AR, (ii) increase stromal activity by stimulating expression of COL1A1 and COL3A1 and (iii) increase the expression of 7 of the 25 PCOS candidate genes. Thus inhibition of TGFβ signalling could be part of the aetiology of PCOS or at least the aetiology of polycystic ovaries. STUDY FUNDING/COMPETING INTEREST(S): Funding was received from Adelaide University China Fee Scholarship (M.L.), Australian Research Training Program (R.A.) and the Faculty of Health and Medical Science Divisional Scholarship (R.A.), Adelaide Graduate Research Scholarships (R.A. and N.A.B.), Australia Awards Scholarship (M.D.H.), Robinson Research Institute Career Development Fellowship (K.H.) and Building On Ideas Grant (K.H.), National Health and Medical Research Council of Australia Centre for Research Excellence in the Evaluation, Management and Health Care Needs of Polycystic Ovary Syndrome (N.A.B., M.D.H. and R.J.R.; GTN1078444) and the Centre for Research Excellence on Women's Health in Reproductive life (R.A., R.J.R. and K.H.; GTN1171592) and the UK Medical Research Council (R.A.A.; grant no. G1100357). The funders did not play any role in the study design, data collection and analysis, decision to publish or preparation of the manuscript. The authors of this manuscript have nothing to declare and no conflict of interest that could be perceived as prejudicing the impartiality of the research reported.